International relations and world politics - Viotti, Paul R. (Pearson, 2013)
This introduction to contemporary international relations focuses on what has changed and what has remained the same since the end of the Cold War.Providing a strong conceptual, historical, and philosophical foundation, it identifies key perspectives (realism and pluralism) and the actors in world politics, explains the concepts, tracks the trends (global interdependence and crises of authority), and examines current and future global concerns.